Cedera Ginjal Akut akibat Glomerulonefritis Akut Pasca-Steptococcus pada Kehamilan - I Dewa Gede Agung Suta Ariwangsa; Nyoman Paramita Ayu (MEDICINUS, 2025)
Acute post-Streptococcal glomerulonephritis (APSGN) is an inflammation of the glomeruli due to immunologic mechanism caused by group A β-hemolytic Streptococcus infection. The clinical triad of APSGN includes are gross or microscopic hematuria, edema (mostly periorbital), and arterial hypertension. This condition is generally self-limiting and is recommended to be managed symptomatically. APSGN rarely occurs in pregnancy, with estimated incidence of 1:40,000.This report discusses a rare case of stage III acute kidney injury due to APSGN in a 36-year-old pregnant woman at 9 weeks of gestation. The patient presented with fever, oliguria, hypertension, and a history of sore throat. Kidney function tests revealed elevated serum creatinine (12.49 mg/dl) and low glomerular filtration rate (GFR) (3.62 ml/minute/1.73 m2). Urinalysis showed proteinuria, microscopic hematuria, leukocytes, and granular cast. No microorganisms were found in the throat swab culture, however the anti-Streptolysin O (ASO) titer was found elevated. A chest X-ray revealed findings consistent with pneumonia. The patient received supportive treatment, including fluid resuscitation, intravenous antibiotic for pneumonia, and underwent several sessions of hemodialysis. On the seventh day of treatment, her kidney functionimproved, and she was discharged five days later. Several previous case reports on APSGN in pregnancy have also indicated a favorable prognosis for both the mother and fetus.